Mothers of invention : women, Italian facism, and culture - Pickering-Iazzi, Robin (University of Minnesota Press, 1995)
This volume is the first thorough investigation of culture produced by Italian women under Fascism (1922-1943). In literature, painting, sculpture, film, and fashion, the contributors explore the politics of invention articulated by these women as they negotiated prevailing ideologies.